2021
DOI: 10.1039/d0ra08427a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of the non-thermal effect in microwave induced polymer curing

Abstract: The non-thermal effect of microwave was evaluated quantitatively by the calculation of activation energy and pre-exponential factors with an isothermal microwave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Proposed rationale, analysis and conclusions on kinetics‐enhancements in IMACS are fully supported by relevant process‐kinetics data obtained from various types of microwave‐assisted syntheses: (1) inorganic syntheses—copper oxide reduction, 18,44 carbon oxidation, 45 (2) organic syntheses—fullerol formation, 46 quaternary ammonium salt synthesis, 47 polyamid acid synthesis, 48 and (3) polymeric syntheses—carvone isomerization, 49 acrylic acid crosslinking/polymerization, 50 epoxy resin curing, 51 and solution imidization 52 …”
Section: Characterizing the Kinetics Of Imacs Using The Degenerate Upkementioning
confidence: 74%
See 2 more Smart Citations
“…Proposed rationale, analysis and conclusions on kinetics‐enhancements in IMACS are fully supported by relevant process‐kinetics data obtained from various types of microwave‐assisted syntheses: (1) inorganic syntheses—copper oxide reduction, 18,44 carbon oxidation, 45 (2) organic syntheses—fullerol formation, 46 quaternary ammonium salt synthesis, 47 polyamid acid synthesis, 48 and (3) polymeric syntheses—carvone isomerization, 49 acrylic acid crosslinking/polymerization, 50 epoxy resin curing, 51 and solution imidization 52 …”
Section: Characterizing the Kinetics Of Imacs Using The Degenerate Upkementioning
confidence: 74%
“…In the field of microwave‐augmented chemistry, rate‐enhancements of isothermal chemical (inorganic, organic, or polymeric) syntheses conducted under resonant microwave (RM) irradiation versus their counterpart processes activated by conventional (field‐free) heating have been widely recognized. Typical kinetic data obtained from syntheses under both conventional field‐free heating and RMF heating conditions are tabulated and compared in Table 1 18,44–52 . Evidently, kinetics‐enhancements of chemical reactions conducted under…”
Section: Characterizing the Kinetics Of Imacs Using The Degenerate Upkementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the 3D-printed object was exposed to microwave irradiation for effectively strengthening the shape-retention, layer bond strength, and mechanical properties, and the schematic of microwave effect is illustrated in Fig. S13 † 1,32 . Furthermore, the multilayer geometries were printed with remarkable shape-fidelity and accuracy, such as ‘BUCT’ models, cube, circular ring, wheel gear, five-pointed star, and cellular architecture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Microwave is a cleaner and greener energy resource to drive the chemical reactions, and it has advantages in terms of extraordinary efficiency and high yield. The applications of microwave in chemical reactions are very wide, such as organic synthesis, biomass treatment, and nanomaterials. Most accelerating chemical reactions under the microwave irradiation can be explained by the microwave thermal effect. , Numerous experimental studies determine that not only the microwave thermal effect but also the microwave nonthermal effect play a decisive role in enhancing chemical reactions. Tiwari et al demonstrated the simultaneous activation of CH 4 and N 2 in a microwave catalytic reaction to produce NH 3 and C 2 products and found that the elementary reaction steps leading to NH 3 synthesis occurs due to the nonthermal effects of microwave irradiation. Silva et al verified that the combination of thermal and nonthermal effects during the microwave-assisted hydrothermal treatment provides ideal conditions for an efficient and rapid synthesis of pristine SrTiO 3 mesocrystals.…”
Section: Introductionmentioning
confidence: 99%